2014
DOI: 10.1371/journal.pcbi.1003465
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome-Scale Reconstruction of Gapless Metabolic Networks for Present and Ancestral Species

Abstract: We introduce a novel computational approach, CoReCo, for comparative metabolic reconstruction and provide genome-scale metabolic network models for 49 important fungal species. Leveraging on the exponential growth in sequenced genome availability, our method reconstructs genome-scale gapless metabolic networks simultaneously for a large number of species by integrating sequence data in a probabilistic framework. High reconstruction accuracy is demonstrated by comparisons to the well-curated Saccharomyces cerev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 40 publications
(54 reference statements)
2
77
0
Order By: Relevance
“…Using the homology search results, the probability of observing each enzyme is scored for each species. This score is based on the probabilistic model that takes into account both BLAST and GTG and it has been shown that the inclusion of GTG improves the reconstructions [21]. Previously, the score was computed as an average of these two sources of information.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the homology search results, the probability of observing each enzyme is scored for each species. This score is based on the probabilistic model that takes into account both BLAST and GTG and it has been shown that the inclusion of GTG improves the reconstructions [21]. Previously, the score was computed as an average of these two sources of information.…”
Section: Resultsmentioning
confidence: 99%
“…In the second phase of the CoReCo algorithm, the metabolic network is reconstructed using an algorithm that creates gapless metabolic networks [21]. The reactions are added to the network in an iterative manner, starting from the highest-scoring reactions, and subsequently adding reactions until the remaining reactions have a score lower than a user-defined threshold .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The used systems metabolic engineering strategies may be useful for the construction of versatile B. subtilis cell factories for the production of the other industrially important chemicals. Method: Our CoReCo method [1] reconstructs genome-scale gapless metabolic networks simultaneously for a large number of species by integrating sequence data in a probabilistic framework. Our comparative approach is particularly useful in scenarios where the quality of available sequence data is lacking, and when reconstructing evolutionary distant species, such as genomes assembled from metagenomics data.…”
Section: Long Liumentioning
confidence: 99%